A comprehensive evaluation of CHEK2 germline mutations in men with prostate cancer. Issue 8 (9th March 2018) - Wu, Yishuo; Yu, Hongjie; Zheng, S. Lilly; Na, Rong; Mamawala, Mufaddal; Landis, Tricia; Wiley, Kathleen; Petkewicz, Jacqueline; Shah, Sameep; Shi, Zhuqing; Novakovic, Kristian; McGuire, Michael; et al.
Abstract : Background: Germline mutations in CHEK2 have been associated with prostate cancer (PCa) risk. Our objective is to examine whether germline pathogenic CHEK2 mutations can differentiate risk of lethal from indolent PCa. Methods: A case‐case study of 703 lethal PCa patients and 1455 patients with low‐risk localized PCa of European, African, and Chinese origin was performed. Germline DNA samples from these patients were sequenced for CHEK2 . Mutation carrier rates and their association with lethal PCa were analyzed using the Fisher exact test and Kaplan‐Meier survival analysis. Results: In the entire study population, 40 (1.85%) patients were identified as carrying one of 15 different germline CHEK2 pathogenic or likely pathogenic mutations. CHEK2 mutations were detected in 16 (2.28%) of 703 lethal PCa patients compared with 24 (1.65%) of 1455 low‐risk PCa patients ( P  = 0.31). No association was found between CHEK2 mutation status and early‐diagnosis or PCa‐specific survival time. However, the most common mutation in CHEK2, c.1100delC (p.T367 fs), had a significantly higher carrier rate (1.28%) in lethal PCa patients than low‐risk PCa patients of European American origin (0.16%), P  = 0.0038. The estimated Odds Ratio of this mutation for lethal PCa was 7.86. The carrier rate in lethal PCa was also significantly higher than that (0.46%) in 32 461 non‐Finnish European subjects from the Exome Aggregation Consortium (ExAC) ( P  = 0.01). Conclusions: While overall CHEK2 mutations were not significantly more common in men with lethal compared to low‐risk PCa, the specific CHEK2 mutation, c.1100delC, appears to contribute to an increased risk of lethal PCa in European American men.